The History of Psychology in Brazil - Campos, Regina Helena de Freitas (Oxford Research Encyclopedia of Psychology, 2021)
Studies of the history of Brazilian psychology generally focus on the reception and circulation of Western psychological theories and techniques and their application in research and practice within the country. This approach must be complemented by studying the transformation and production of psychological knowledge originating in Brazilian culture, including its popular levels, and its interaction with imported ideas. There are at least four sources that participate in the formation of Brazilian culture: the native Indians’ ideas on human nature and development; the contributions of African culture to the understanding of the psychological world brought by the Africans sold into slavery and transferred to Brazil between the 16th and the 19th centuries; European views received through the teaching of philosophical psychology, introduced into Catholic educational institutions in colonial times; and scientific psychology, introduced into public medical schools and teacher training institutions from the 19th century onward. The profession of psychologist, born of the confluence of the professions of physician and educator, was regulated in 1962. The tasks of the psychologist were then defined: psychological evaluation through mental tests and the diagnosis of mental and behavioral troubles, psychological guidance, and psychotherapy. The profession was primarily designed for the intellectual and social elites. From the 1990s onward, with the increasing numbers of graduates, the participation of psychologists in public health, education, and social services institutions expanded rapidly. In consequence, psychologists began to develop intervention practices and techniques more fitted to the demands of the low-income population, immersed in the beliefs and practices of Brazilian popular culture. This dialogue contributed to the construction of innovations in psychology, making it more sensitive to the worldviews arising from the cultures that compose the Brazilian cultural landscape and producing original contributions with a profound impact on modern psychology. Today, Brazilian psychology professionals constitute one of the largest communities of psychologists in the world, with a strong presence in mental health, educational, and social services networks. The work of psychologists, strongly influenced by theoretical perspectives that emphasize the relationship between sociocultural dynamics and psychological elaboration, is at present considered relevant in the realization of human rights ideals.